Seismically-induced soft-sediment deformation structures associated with the Magallanes–Fagnano Fault System (Isla Grande de Tierra del Fuego, Argentina) - Onorato, María Romina; Perucca, Laura Patricia A.; Coronato, Andrea Maria Josefa; Rabassa, Jorge Oscar; Lopez, Carlos Ramiro (Sedimentary Geology)
In this paper, evidence of paleoearthquake-induced soft-sediment deformation structures associated with the Magallanes–Fagnano Fault System in the Isla Grande de Tierra del Fuego, southern Argentina, has been identified. Well-preserved soft-sediment deformation structures were found in a Holocene sequence of the Udaeta pond. These structures were analyzed in terms of their geometrical characteristics, deformation mechanism, driving force system and possible trigger agent. They were also grouped in different morphological types: sand dykes, convolute lamination, load structures and faulted soft-sediment deformation features. Udaeta, a small pond in Argentina Tierra del Fuego, is considered a Quaternary pull-apart basin related to the Magallanes–Fagnano Fault System. The recognition of these seismically-induced features is an essential tool for paleoseismic studies. Since the three main urban centers in the Tierra del Fuego province of Argentina (Ushuaia, Río Grande and Tolhuin) have undergone an explosive growth in recent years, the results of this study will hopefully contribute to future analyses of the seismic risk of the region. Fil: Onorato, María Romina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina. Universidad Nacional de Tierra del Fuego, Antártida e Islas del Atlántico Sur. Instituto de Ciencias Polares, Recursos Naturales y Ambiente. Departamento de Biología; Argentina Fil: Perucca, Laura Patricia A. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Universidad Nacional de San Juan. Facultad de Ciencias Exactas, Físicas y Naturales. Instituto de Geología "Dr. Emiliano Aparicio". Gabinete de Neotectónica y Geomorfología; Argentina Fil: Coronato, Andrea Maria Josefa. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina. Universidad Nacional de Tierra del Fuego, Antártida e Islas del Atlántico Sur. Instituto de Ciencias Polares, Recursos ...